DAMPAK KEBIJAKAN DESENTRALISASI FISKAL TERHADAP TINGKAT KETIMPANGAN PENDAPATAN UNTUK PROVINSI DI INDONESIA - tiana wijoyo (Universitas Djuanda Bogor, 2011)
Economical discrepancy and imbalance in distributing revenue between high income and low income group of people added by poverty level or the number of people under poverty line become two biggest issues in many developing countries, including Indonesia. Various efforts have been conducted by the Government in order to suppress that discrepancy. One of the policies is by launching Law No.22/1999 and Law No. 25/1999 which stipulate local government policy and fiscal decentralization. The study aims to identify the impact of such policies toward revenue discrepancy among provinces in Indonesia. The method used in this study is Index Williamson and double regression econometric model. The result of the study shows that income discrepancy level among provinces is high. While estimation result for used model shows that fiscal decentralization contributes positive and significant impact statistically toward income discrepancy level among provinces in Indonesia. However, fiscal transfer discrepancy contributes negative significant impact statistically toward income discrepancy. Local revenue (PAD) discrepancy contributes positive and significant impact statistically toward income discrepancy.